Limitations and Strengths of Doppler/Echo Pulmonary Artery Systolic Pressure–Right Heart Catheterization Correlations: A Systematic Literature Review. Issue 1 (25th March 2014) - Finkelhor, Robert S.; Lewis, Steven A.; Pillai, Dilip
<x xml:space="preserve">Abstract</x> Aims Because many recent studies have questioned the accuracy of Doppler echocardiography (D) in determining pulmonary artery systolic pressure (PASP), we performed a detailed literature analysis attempting add clarity. Methods and Results Studies through 2011 comparing D and right heart catheterization (RHC) PASP, with at least 25 studied patients and reporting correlation coefficients (r) were identified. Patient demographics, study characteristics, the percent of patients studied for left or right heart pathologies, and study biases were determined. After adjusting for differing study sizes, each study's r value was used as a single datapoint and dichotomized above or below the entire cohort's mean values. From 32 studies 2604 D‐RHC parings were reported. Their overall weighted r was 0.68 ± 0.19. Poorer correlations were found for right heart pathologies compared to left heart pathologies (r = 0.58 vs. 0.84, P < 0.001) and for normal PASP patients in a study compared to abnormal PASP patients (r = 0.55 vs. 0.82, P < 0.001). Studies with predominately right heart pathology had a significantly greater D‐RHC time difference, fewer successful D determinations, a greater percentage of normal PASPs on RHC, and more between‐method differences >10 mmHg. Metaregression analyses indicated that both right heart pathology predominance and a greater percent of normal PASPs on RHC remained associated with poorer correlations. Conclusions D PASP‐RHC correlations were high and between‐method differences less in patients with left heart pathology but were poorer for right heart diseases and studies with proportionately more normal PASPs on RHC for which further study is needed.